Seedling age of Abies georgei var. smithii reveals functional trait coordination in high-altitude habitats in southeast tibet - Zhang, Xinsheng; Zhao, Ningning; Zhou, Chenni; Lu, Jie; Wang, Xiangtao (Frontiers in Ecology and Evolution, 2022)
Functional trait-based plant ecology is often used to study plant survival strategies and growth processes. In this work, the variation regularity of functional traits and their correlations were studied in Abies georgei var. smithii seedlings of different seedling ages found along the altitude gradient (3,800–4,400 m) in Sejila Mountain, Southeast Tibet. The following functional traits of seedlings in five age classes were determined: above-ground functional traits∼leaf thickness (T), leaf area (LA), specific leaf area (SLA), and leaf dry matter content (LDMC); below-ground functional traits∼specific stem length (SSL), specific root length (SRL), specific root surface area (SRA), root tissue density (RTD), and root dry matter content (RDMC). Results showed that (1) except for LDMC, most of the functional traits of the seedlings at different altitudes showed a regular change trend over time. The changes in traits caused by seedling age had significant effects on other traits (p < 0.05). Altitude only had significant effects on T, LA, SLA, SRA, RTD, and RDMC (p < 0.05). (2) The correlation between the above- and below-ground traits was more significant in 5-6-year-old seedlings than in other age classes (p < 0.05). Principal component analysis (PCA) results showed that LA and SLA were the dominant traits of fir seedlings in five age categories Pearson correlation analysis indicated a correlation between RTD and above-ground traits, thus validating the correlation between the above- and below-ground traits of seedlings of Abies georgei var. smithii of different ages. (3) Available potassium, total potassium, and total organic carbon (TOC) had the greatest influence on the traits of 5-6-year-old seedlings. This study revealed that the functional traits of Abies georgei var. smithii seedlings at different altitudesdynamically change with seedling age. The findings help in understanding the growth strategies of seedlings during early development. Future research on the combination of soil factors and seedling traits will provide a theoretical basis for artificial cultivation and protection of native vegetation.